The roly-poly pudding. - Potter, Beatrix, 1866-1943. (New York : F. Warne & Co., Inc., 1908)
Tom Kitten hides from his mother and is caught by rats who want to make him into a kitten dumpling.
Keywords: Cats -- Fiction; Rats -- Fiction; Animals -- Fiction